In-situ quantitation of genome release of Japanese encephalitis viruses by quantum dot-based single-virus tracking. (October 2021) - Liu, Hao-Yang; Wang, Zhi-Gang; Hu, Yusi; Shi, Xue-Hui; Chen, Hua-Jie; Li, Xiao; Liu, Shu-Lin; Pang, Dai-Wen
Highlights: A strategy for dual-labeling of viral envelope and genome with QDs and multiple molecular beacons (MMBs) was developed. The combination of SVT and the in-situ pH quantification of endosomal acidification during viral infection was achieved. Our results showed that the specific virus-endosome fusion events of JEV predominantly occurred in the maturing endosomes. We addressed the question that where and how the viruses harness endosomal compartments and release their genome. Graphical Abstract: ga1 Abstract: The fusion of the viral membrane and genome release are hallmark events of enveloped virus infections. However, the related dynamic mechanisms of most viruses remain poorly understood. In this study, we combine single-virus tracking with the in-situ pH quantification of the dual-labeled Japanese encephalitis virus (JEV) to label its viral envelope and RNA by using quantum dots and pH-sensitive dyes, respectively. This robust technique allows us to visualize and quantify the process of genome release at the level of a single virus in real time, and to thus collect more information on the dynamics of genome release. The results of our experiments show that the infection pathway of the JEV is dependent on actin and microtubules, and viral fusion events predominantly occur in maturing endosomes that represent the intermediate stage between early and late endosomes. The kinetic insights gained in this study address long-standing questions regarding where and how the JEV harnesses endosomal compartments and releases its genome for replication, and are expected to facilitate a comprehensive understanding of the infection mechanism of JEV.